A Preliminary Study of the Treatment Outcomes of Paediatric Dental Patients Referred for General Anaesthesia or Sedation at a Regional Hospital in Trinidad - Tricia Percival; Reshma Bhagoutie (MDPI AG, 2021)
General anaesthesia and sedation are known to be useful adjuncts in the care of paediatric dental patients. There are several challenges that prevent patients from receiving care. Aim: To assess the treatment outcomes of paediatric dental patients seen at an emergency facility who were referred for treatment under sedation or general anaesthesia at a regional hospital in Trinidad. Methods: Records of patients seen at the Child Dental Health Unit Emergency clinic at the University of The West Indies Dental School from 2012 to 2017 were assessed. The parents of children referred for general anaesthesia or sedation at the regional hospital were then interviewed via telephone. Results: Most children (53.4%) were younger than 6 years old and the most common reasons for referral were the treatment of multiple carious teeth and behaviour management. Furthermore, 66.1% of cases did not receive treatment and had a mean waiting time of 4.7 years, and 61.7% of referred cases needed emergency care while awaiting general anaesthesia or sedation. Limited access to these services and the high cost of treatment were the main reasons for non-treatment. Conclusion: There is significant need for the timely treatment of paediatric dental patients referred for general anaesthesia or sedation. Improved availability and accessibility of these services could improve patients' quality of life.